Molecular farming navigates a complex regulatory landscape - Bobo, Jack (Frontiers in Plant Science, 2024)
Molecular farming, the practice of engineering plants to produce animal recombinant proteins, presents novel challenges and opportunities for domestic markets and international trade. This article explores the multifaceted risks associated with these biotechnological advancements, including public health concerns related to new recombinant animal proteins produced in plants, crosscontamination and unintended allergens, and the necessity for stringent identity preservation systems to avoid past failures. On the global stage, the trade of such genetically engineered crops brings about unique regulatory concerns, underscoring the need for internationally harmonized policies and reevaluating existing low-level presence (LLP) thresholds to address unexpected allergens. Moreover, molecular farming ventures into complex religious and ethical territories, particularly affecting communities with strict dietary laws, such as Islamic, Jewish, and those following vegan or vegetarian lifestyles. Addressing these concerns requires a collaborative approach among scientists, regulatory bodies, industry leaders, and religious figures, aiming to foster an inclusive dialogue that navigates the ethical, religious, and environmental implications of integrating animal proteins into plant-based systems. Such efforts are essential for ensuring the responsible development of molecular farming technologies, contributing to a future of sustainable, secure, and inclusive food systems that respect diverse cultural and ethical values.